One lonely sea horse - Freymann, Saxton; Elffers, Joost (New York : Arthur A. Levine, 2000)
One lonely sea horse learns that she has a lot of friends-- friends she can really "count" on.
School Library Journal
Book Links (A.L.A.)
Bulletin (Center for Children's books)
2.0
K-3
Keywords: Friendship -- Fiction; Sea horses -- Fiction; Marine animals -- Fiction; Counting; Stories in rhyme; Friendship -- Fiction; Sea horse -- Fiction; Marine animals -- Fiction; Counting; Stories in rhyme